Comparison of Female Sexual Function Index in patients with psoriatic and rheumatoid arthritis and healthy controls. (20th June 2019) - Boone, Denise; Ronson, Ashley; Karsh, Jacob
Abstract: Objective: The aim of the recent study was to identify and compare the Female Sexual Function Index (FSFI) of three female populations: those with rheumatoid arthritis (RA), psoriatic arthritis (PsA), and healthy individuals. Methods: In this descriptive correlational study, convenience sampling was used to recruit 50 female RA patients, 36 female PsA patients and 50 healthy women between June and September 2018. Results: The mean ages of the RA patients, PsA patients and healthy controls were, respectively, 53.1 ± 11.8 years, 51.6 ± 13.7 years and 37.4 ± 10.4 years. Controls were significantly younger than RA ( p  < 0.001) and PsA ( p  = 0.002) patients. Data including all participants: Based on the total sexual functioning cut‐off score of 26.55, 68% of RA patients (34/50), 67% of PsA patients (22/33) and 44% of healthy controls (11/25) met the criteria for sexual dysfunction. Data excluding participants who reported not having had sex in the previous month: Controls had significantly higher FSFI scores than the RA patients across all six domains ( p  ≤ 0.001) and the overall score ( p  < 0.001). Controls had significantly higher FSFI scores than the PsA patients across four of the six domains ( p  ≤ 0.026) and the overall score ( p  = 0.008). There were no statistically significant differences between the RA and PsA groups. Patient pain, patient global status and Health Assessment Questionnaire scores were not significantly correlated with the total FSFI score in either PsA or RA. Conclusions: These findings demonstrate that decreased sexual functioning is more common in women with RA and PsA when compared with controls. All female patients with RA and PsA should be screened for sexual dysfunction.